PENDAMPINGAN LITERASI AKAD LEMBAGA KEUANGAN SYARI'AH PADA KOPERASI BUEKA AS-SAKINAH KABUPATEN MALANG - Fitrian Aprilianto (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2021)
Purpose of the study: The data that needs there is an option for cooperatives to run their operations based on sharia, so many cooperatives with conventional principles take the initiative to convert their operational activities to change their basis to sharia. However, in practice, there are still obstacles from the internal cooperative itself. The purposes of this service are to provide understanding to the administrators of the Bueka As-Sakinah cooperative, Malang Regency, on contracts in Islamic financial institutions and their implementation in sharia cooperatives Methodology: In this study, the implementation method is divided into three parts: First, in the preliminary stage, the service team will agree with partners related to the main problems that can be solved. Second, the observation stage can be carried out to explore the problem faced by the Bueka As-Sakinah Cooperative. Third, the implementation stage is the next step or stage that is practical and directly in contact with the activity participants Main Findings: During the service process, it was found that most of the conditions for the management of the Bueka As-Sakinah Cooperative, Malang Regency, did not understand the concept of Islamic finance, especially understanding the contracts used for the cooperative's products. Previously there had been efforts from the cooperative to make a draft contract or contract with sharia principles, but the management and supervisors did not understand the contract used so that the cooperative members did not get clarity regarding the contract. Applications of this study: One of the cooperatives under the auspices of the management of 'Aisyiyah which is in the process of converting to a sharia cooperative is the Bueka As-Sakinah Cooperative, Malang Regency. Bueka As Sakinah Cooperative is a savings and loan cooperative that was established in 1995 and obtained a legal entity on November 30, 1998 Novelty/Originality of this study: In this service, we have been able to identify the problems experienced by the cooperative, especially the problem of human resources or the ability of the management to understand contracts in Islamic financial institutions Based on these problems we provide solutions by providing material on the basic concepts of Islamic financial institutions with lecture methods and interactive dialogue in the form of question and answer.